At the Pond : Comparing Numbers - Gould, Jane (Huntington Beach, CA : T Teacher Created Materials, 2012)
This reader shows students how to compare quantities as they read about life in a pond. Students must count to find out how many plants or animals are in the photographs. Then students compare the quantities of two plants or animals. The text introduces the comparing terms: more, less, and equal.
Includes answer key
Keywords: Pond animals -- Juvenile literature; Counting -- Juvenile literature